Depressive symptoms and mental representations in a sample of pregnant Italian women during COVID-19: comparison of primipara and multipara - Lucia Ponti; Martina Smorti; Chiara Ionio; Giulia Mauri; Alessia Carducci (Hygeia Press di Corridori Marinella, 2023)
During the COVID-19 outbreak, the risk of depression has increased for pregnant women and especially for first-time mothers-to-be. Pre-COVID-19 literature showed that depression is negatively linked to mental representations during pregnancy. This pilot study explored the difference in depressive symptoms and maternal representations style in primiparous and multiparous pregnant women during the outbreak of COVID-19 (2020-2021). 25 women (14 primiparous, 11 multiparous) were recruited in their last trimester of pregnancy. Participants responded to the Edinburgh Postnatal Depression Scale (EPDS) and Interview for Maternal Representations during Pregnancy (Intervista sulle Rappresentazioni Materne in Gravidanza - IRMAG). Results showed that primiparous women presented higher depressive symptoms than multiparous ones. Moreover, primiparous women reported lower richness of perception (p = 0.008), openness to change (p = 0.035) and dominance of fantasies (p = 0.000) in maternal representation and, globally, more restricted representations (71.4%) than multiparous ones (18.2%) (p = 0.020). Mental representations were related to the level of depression, with integrated representations being associated with lower depression than restricted and ambivalent ones (p = 0.001). A preventive intervention to support primiparous pregnant women during future pandemics would be necessary in particular to avoid negative repercussions also in the post-partum experience. This paper is part of the "Pediatric Psychology and Related Issues" Section (Sezione "Psicologia Pediatrica e Dintorni") by S.I.P.Ped. (Italian Society of Pediatric Psychology, Società Italiana di Psicologia Pediatrica).